2014
DOI: 10.1007/s11136-014-0894-2
|View full text |Cite
|
Sign up to set email alerts
|

Health status and quality of life: results from a national survey in a community-dwelling sample of elderly people

Abstract: HRQoL is globally preserved in older adults in Switzerland, even if substantial impairment is reported in very old age affecting mainly functional health dimensions. Anxiety/Depression and Pain/Discomfort did not appear to be affected by age; high rates of difficulties were reported for Pain/Discomfort but not for Anxiety/Depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
30
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 41 publications
13
30
3
1
Order By: Relevance
“…Education has been sometimes used as a way to address socioeconomic status (SES) inequalities connected to health and QoL: our findings show that lower educational levels are associated to diminished QoL compared to having high school or academic degrees. Similar results were found among participants to the American Health and Retirement Study and to the English Longitudinal Study of Ageing [ 41 ], as well as among community-dwelling elderly individuals (aged 65+) from Switzerland [ 42 ]. As previously reported [ 16 ] people with low SES seem to face a double burden: first, increased levels of health impairments and, second, lower QoL once health is impaired.…”
Section: Discussionsupporting
confidence: 73%
“…Education has been sometimes used as a way to address socioeconomic status (SES) inequalities connected to health and QoL: our findings show that lower educational levels are associated to diminished QoL compared to having high school or academic degrees. Similar results were found among participants to the American Health and Retirement Study and to the English Longitudinal Study of Ageing [ 41 ], as well as among community-dwelling elderly individuals (aged 65+) from Switzerland [ 42 ]. As previously reported [ 16 ] people with low SES seem to face a double burden: first, increased levels of health impairments and, second, lower QoL once health is impaired.…”
Section: Discussionsupporting
confidence: 73%
“…The distribution of VAS values in the same age categories was quite stable, and the decline in VAS values by increasing age [ 31 ] resembles the proportions from 2006 [ 19 ]. Age-related deterioration in VAS values and health status is seen in other studies [ 32 , 33 , 34 ] for men and women as well as people with problems and those without. Our participants in the best health state showed an average VAS score of 91.9.…”
Section: Discussionsupporting
confidence: 59%
“…Luthy et al reported that male gender was associated with better HRQoL, whereas their female counterparts were manifested with specific problems with aging, such as loneliness, handicaps, a longer duration of symptoms prior to death. They also revealed that higher educational background was associated with better HRQoL [10]. Varma et al demonstrated that the elderly Indians living at their homes yielded higher HRQoL compared with those residing in the community [11].…”
Section: Introductionmentioning
confidence: 99%